VALUASI EKONOMI SUMBERDAYA PERIKANAN TANGKAP DI DANAU KAJUIK PELALAWAN RIAU - marisa_hutagalung marisa_hutagalung; Hendrik_hendrik Hendrik_hendrik; Trisla_warningsih Trisla_warningsih (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study aims to identify the potential of capture fisheries resources by calculating the economic value of analyzing the economic value of Lake Kajuik fishery resources. Research Methods by Identifying Potential Fishery Resources and Effect of Production (EoP) Method with Consumer Surplus Approach. This research was conducted on May - June 2017 at Kajuik Lake, Langgam District, Pelalawan Regency with 30 respondents with lake 42,5 ha and 22,5 ha wide. The result of the research concludes that in calculating the economic value of capture fishery resources by using Effect of Production (EoP) calculation with consumer surplus value (CS) is obtained Rp 25,017,747 per fisherman per year. The economic value of fisheries capture fishery resources of Lake Kajuik is obtained at Rp 46,699,794 per hectare.